Effectiveness of Structured Teaching Program on Knowledge Regarding Biomedical Waste Management among 1st Year B. Sc. Nursing Students of Selected Nursing Colleges at Bangalore - Sajji, Asha; Vadagaonkar, Maya (International Journal of Nursing Research, 2023)
Background: Waste produced from the health-care facilities is deleterious and hazardous. Inadequate understanding and improper handling of biomedical waste can give rise to serious threat not only to the health of health-care personnel but also the society and environment as whole. Objective: The objective of this study was to determine the efficacy of structured teaching program on knowledge regarding biomedical waste management. Materials and Methods: A pre-experimental one group pre-test post-test study was conducted among 60 1st year basic B.Sc. nursing students who were chosen using a purposive sampling technique. A pre-test was conducted using a self-administered knowledge questionnaire with 30 items followed by which structured teaching program was conducted. Post-test was conducted after 1 week using afore-mentioned questionnaire. Results: The findings of the present study revealed that, in pre-test, majority 87% subjects under study had inadequate knowledge, 10% had moderately adequate knowledge, and only 3% participants had adequate knowledge. In post-test, majority 78% study subjects had adequate knowledge, 22% had moderately adequate knowledge, and no one remained with inadequate knowledge regarding biomedical waste management. There was a significant difference between the mean scores of knowledge of nursing students regarding biomedical waste management as the “t” value obtained 29.932 was higher than the tabulated value at P < 0.05 level of significance. Conclusion: Teaching program is effective in creating the awareness and improving the knowledge of the study participants regarding biomedical waste management.